Optimisation of extraction method for quantification of free fatty acids in oat-, pea- and faba-bean-based protein sources by liquid chromatography coupled with mass spectrometry - Anastassia Zeinatulina; Aleksei Kaleda; Maria Kuhtinskaja; Tiina Kriščiunaite (NFS Journal)
Plant-based protein sources, including oat, pea, and faba bean, are widely used in milk and meat alternatives. However, these crops can be inherently bitter, which limits their use in some food products. Processing into flours, protein concentrates, and isolates may cause changes in chemical composition and influence bitterness. We present an optimised and validated LC-MS method using isopropanol:methanol (1:1, v/v) solvent extraction to determine selected bitter-tasting free fatty acids (FFAs). Accurate quantification of FFAs (linolenic, myristic, palmitic, linoleic, oleic, and stearic acids) was achieved using isotopically labelled oat flour extract as an internal standard. The total FFA content in whole grain oat flour, oat protein concentrate, pea flour and protein isolate, and faba bean flour and protein isolate ranged from 4.4 to 3841 mg/100 g dry weight. FFA analysis aids in assessing bitterness and selecting processing techniques to reduce these compounds in plant-based foods.